(untitled) (Praxis Educativa, 2012)
This paper is based on the professional biographies of six professors identified as excellent by senior students in three programmes at the School of Humanities, Mar del Plata State University. In-depth interviews examined the teachings and practices these instructors encountered along their educational biographies in order to find traces of these experiences in their current lives. The aim is to disclose the subtle ways in which the past influences their academic present. The life histories retrieved reveal the importance of the actors’ mentors at the onset of their teaching and research at the university. Th e recovery of these memories allows the conceptualization of experts’ role in the education of novices, thus examining what is traditionally considered as the informal supervision of teaching assistants and junior researchers. In this way, we try to create a site at the university where it is possible to discuss mentors’ good practices.